Next Generation Therapeutic Strateg‐Es: Evolving cancer immunotherapy through agents that Engage, Expand and Enable the anti‐tumor immune response. Issue 1 (21st January 2021) - Wolfson, Benjamin; Hodge, James W.
Abstract: The development and FDA approval of immune checkpoint blocking antibodies have brought new light to cancer immunotherapy. While immune checkpoint blockade (ICB) has demonstrated clinical benefit in certain tumors as monotherapy, effective therapy of established tumors necessitates a combination of multiple immuno‐oncology agents targeting diverse functions of the immune system. These combination strategies should be tactically designed to Engage the immune system by inducing a tumor‐antigen specific T‐cell population, Expand the number of antigen‐specific cytotoxic T cells and increase their migration to the tumor microenvironment, and once there, Enable prolonged and persistent effector function. Although viral therapeutic cancer vaccines have demonstrated little efficacy as monotherapies, they have substantial potential to Engage the immune system as one branch of a multipronged treatment strategy. This review will summarize prior and ongoing Phase II and III clinical trials built upon the foundation of viral therapeutic cancer vaccines. We examine their efficacy as a monotherapy, and more importantly, when combined with additional agents that Expand and Enable the immune system. It is clear that the future of cancer immunotherapy will include evolving treatment strategies made up of multiple agents, and we are optimistic that in this context viral therapeutic cancer vaccines will emerge as an important part of next generation effective therapeutic strategies.